RECENT SILICIC VOLCANISM IN THE BACK-ARC ZONE OF THE KOMANDORSKIY ISLANDS (NEW DATA) - Tsvetkov A.A. (My University, 1990)
In this paper we present and discuss new data on the petrography and chemistry of the principal ore-forming minerals in the lavas of the Piyp volcano and investigate their geochemistry; the data include the first determinations of the short-lived cosmic isotope 10Be and the isotopic ratios 87Sr/86Sr and 143Nd144Nd.